The concentration and growth of solids in fragmenting circumstellar disks - Baehr, Hans-Paul Frederick; Klahr, Hubert (The astrophysical journal, 2019)
Due to the gas-rich environments of early circumstellar disks, the gravitational collapse of cool, dense regions of the disk form fragments largely composed of gas. During formation, disk fragments may attain increased metallicities as they interact with the surrounding disk material, whether through particle migration to pressure maxima or through mutual gravitational interaction. In this paper, we investigate the ability of fragments to collect and retain a signiﬁcant solid component through gas-particle interactions in high-resolution 3D self-gravitating shearing-box simulations. The formation of axisymmetric perturbations associated with gravitational instabilities allows particles of intermediate sizes to concentrate through aerodynamic drag forces. By the onset of fragmentation, the masses of local particle concentrations within the fragment are comparable to that of the gas component and the subsequent gravitational collapse results in the formation of a solid core. We ﬁnd that these cores can be up to several tens of Earth masses, depending on grain size, before the fragment center reaches temperatures that would sublimate solids. The solid fraction and total mass of the fragment also depend on the metallicity of the young parent protoplanetary disk, with higher initial metallicities resulting in larger fragments and larger solid cores. Additionally, the extended atmospheres of these soon-to-be gas giants or brown dwarfs are occasionally enriched above the initial metallicity, provided no solid core forms in the center, and are otherwise lacking in heavier elements when a core does form.